Adiponectin has a pivotal role in the cardioprotective effect of CP‐3(iv), a selective CD36 azapeptide ligand, after transient coronary artery occlusion in mice. Issue 2 (4th January 2018) - Huynh, David N.; Bessi, Valérie L.; Ménard, Liliane; Piquereau, Jérôme; Proulx, Caroline; Febbraio, Maria; Lubell, William D.; Carpentier, André C.; Burelle, Yan; Ong, Huy; Marleau, Sylvie
Abstract : CD36 is a multiligand receptor involved in lipid metabolism. We investigated the mechanisms underlying the cardioprotective effect of CP‐3(iv), an azapeptide belonging to a new class of selective CD36 ligands. The role of CP‐3(iv) in mediating cardioprotection was investigated because CD36 signaling leads to activation of peroxisome proliferator–activated receptor‐γ, a transcriptional regulator of adiponectin. CP‐3(iv) pretreatment reduced infarct size by 54% and preserved hemodynamics in C57BL/6 mice subjected to 30 min coronary ligation and reperfusion but had no effect in CD36‐deficient mice. The effects of CP‐3(iv) were associated with an increase in circulating adiponectin levels, epididymal fat adiponectin gene expression, and adiponectin transcriptional regulators ( Pparg, Cebpb, Sirt1 ) after 6 h of reperfusion. Reduced myocardial oxidative stress and apoptosis were observed along with an increase in expression of myocardial adiponectin target proteins, including cyclooxygenase‐2, phospho‐AMPK, and phospho‐Akt. Moreover, CP‐3(iv) increased myocardial performance in isolated hearts, whereas blockade of adiponectin with an anti‐adiponectin antibody abrogated it. CP‐3(iv) exerts cardioprotection against myocardial ischemia and reperfusion (MI/R) injury and dysfunction, at least in part, by increasing circulating and myocardial adiponectin levels. Hence, both paracrine and endocrine effects of adiponectin may contribute to reduced reactive oxygen species generation and apoptosis after MI/R, in a CD36‐dependent manner.—Huynh, D. N., Bessi, V. L., Ménard, L., Piquereau, J., Proulx, C., Febbraio, M., Lubell, W. D., Carpentier, A. C., Burelle, Y., Ong, H., Marleau, S. Adiponectin has a pivotal role in the cardioprotective effect of CP‐3(iv), a selective CD36 azapeptide ligand, after transient coronary artery occlusion in mice. FASEB J. 32, 807–818 (2018). www.fasebj.org